Luminescent lanthanide complexes for reactive oxygen species biosensing and possible application in Alzheimer's diseases. (19th May 2021) - Galaup, Chantal; Picard, Claude; Couderc, François; Gilard, Véronique; Collin, Fabrice
Abstract : Histopathological hallmarks of Alzheimer's disease (AD) are intracellular neurofibrillary tangles and extracellular formation of senile plaques composed of the aggregated amyloid‐beta peptide along with metal ions (copper, iron or zinc). In addition, oxidative stress is considered as an important factor in the etiology of AD and a multitude of metalloproteins and transporters is affected, leading to metal ion misregulation. Redox‐active metal ions (e.g., copper) can catalyze the production of reactive oxygen species (ROS) in the presence of molecular oxygen and a reductant such as ascorbate. The ROS thus produced, in particular the hydroxyl radical which is the most reactive one, may contribute to oxidative stress conditions. Thus, detecting ROS in vivo or in biological models of AD is of interest for better understanding AD etiology. The use of biocompatible and highly specific and sensitive probes is needed for such a purpose, since ROS are transient species whose steady‐state concentrations are very low. Luminescent lanthanide complexes are sensitive probes that can meet these criteria. The present review focuses on the recent advances in the use of luminescent lanthanide complexes for ROS biosensing. It shows why the use of luminescent lanthanide complexes is of particular interest for selectively detecting ROS ( O 2 · ‐, HO, 1 O2, H2 O2, etc.) in biological samples in the µM‐nM range. It particularly focuses on the most recent strategies and discusses what could be expected with the use of luminescent lanthanide complexes for better understanding some of the molecular mechanisms underlying the development of Alzheimer's disease. Abstract : The detection of reactive oxygen species (ROS) in vivo or in biological systems is of interest for the better understanding of the development of certain pathologies for which oxidative stress plays an important role. The use of luminescent lanthanide complexes seems to be particularly judicious for such purpose because it allows sensitive and selective detection of ROS. ​